Analysis of X-Ray Surface Brightness Radial Profiles in Several Relatively Symmetric Young Supernova Remnants - Jin Cao; Yunyong Tang; Keli Peng; Nan Ding; Jinjie Yu (The Astrophysical Journal)
Based on observations from XMM-Newton, we analyze the surface brightness radial profiles of several young supernova remnants (SNRs) with relatively symmetric structures. The surface brightness data are obtained from the MOS1, MOS2, and PN instruments. We fit these profiles using a phenomenological model combining Gaussian and β models. Our results reveal a significant difference between SNRs with bright shell edges and those with faint shell edges. SNRs with bright shell edges exhibit a surface brightness peak within a certain range. In contrast, SNRs with faint shell edges show a gradual decrease in brightness, indicating differences in the physical mechanisms driving their evolution. Subsequently, we use the Gaussian and β models to fit these profiles. The results effectively reflect their evolutionary trends and brightness distribution, indicating that the internal part of the profiles is generally expressed by the Gaussian models, while the external part is characterized by the β model. Notably, the β -values in our model closely approximate the expansion parameters of the SNRs. This intriguing similarity suggests that detailed analyses of surface brightness radial profiles may provide valuable insights into the expansion dynamics of SNRs.